Error Model in Wavelet-compressed Images (2007)
This article presents the compression of images through the comparison between the Wavelet model and the Fourier model, using the minimization of the error function. The problem studied is specific, it consists in determining a base {ei} that minimizes the error function between the original image and the one recovered after compression. It is noteworthy that there are many applications, for example, in medicine or astronomy, where no deterioration of the image is acceptable because all the information contained, even that which is estimated as noise, is considered essential.